The enlightened nation utopia in the novel El mudo. Secretos de Bogotá, por un bogotano (1848) by Eladio Vergara y Vergara (Anclajes, 2012)
In Eladio Vergara’s writing a subjectivity different from the warrior-conqueror and from the religious one appears. So, the citizen does. This citizen asks himself about his contribution to the nation project, as well as about his individuality. In this article, I will relate the Vergara y Vergara’s novel with some historical events from the early 19th century in Colombia, in order to understand the writer interpretation about such events and his aesthetic proposal. Specifically, in El mudo. Secretos de Bogotá, por un bogotano (1848), the story constitutes dichotomies in relation to the positive and negative aspects of this project, which is necessary for keeping the order and the freedom in the newfound republic. In this way, the novel shows the disjunction between honest republican and hypocritical Jesuit as a summary of the confrontation between liberal project party (enlightened and progressive) and conservative one (fanatical religious and dogmatic) during the early 19th century in Colombia.
Keywords: Colombian novel; 19th century; Eladio Vergara y Vergara; literature; politics